THE ROLE OF ARTIFICIAL INTELLIGENCE IN WEB SITES (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Artificial Intelligence (AI) has emerged as a powerful tool that is revolutionizing various industries, and its impact on web development and websites cannot be understated. In recent years, AI has transformed the way websites are designed, developed, and maintained, enhancing user experience, personalization, and overall efficiency. This abstract explores the role of AI in websites, highlighting its key applications, benefits, and challenges. AI plays a crucial role in website design by automating and streamlining the development process. It enables designers to create visually appealing and user-friendly websites through AI-powered tools that generate layouts, optimize images, and improve responsiveness. By leveraging AI algorithms, developers can automate repetitive tasks, saving time and effort, and focus on higher-level aspects of web development.